DESAIN PENCITRAAN MADRASAH DALAM PEMBANGUNAN PENDIDIKAN NASIONAL (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
An image of Islamic school as high-qualiry institution will he meaningless i fit cannot be identified and the community cannot gain overall benefit. The irony is even the actors of education in Islamic school are unable to recognke and feel the benefit from such quality, hence the development of Islamic school either in the context of state intervention or community participation is not always directed toward a- constructive way. Therefore, the further challenge faced by the education institution of Islamic school is how to make the image of Islamic school as a high-quality institution is recognked by the community. Furthermore, how the image be in- line with the mandate of National Education System Law. This paper actually strives for reviewing the- extent to which a strategic position in national education may be identified and interpreted into a good image design by the community. In addition, it is also prepared to find strategies which may be elaborated in the context of developing the image of. Islamic school so as to be able to give a meaningful contribution to improve the life as a nation.
Keywords: image; Islamic school; national education rystem; development design; strategy.